Zdzisław Zmigryder Konopka – ancient militaty historian, classical philologist, historian of roman law and teacher - Ciesielski, Mariusz (Studia Europaea Gnesnensia, 2022)
Zdzisław Zmigryder-Konopka, Warsaw philologist, historian of the antique military, Roman law and teacher, engaged with antiquity in many ways during his scholarly and teaching career. Above all, however, he was trained as a philologist and for a certain period (when not employed at the university) he was even a teacher of Latin and Greek in secondary schools, where he enjoyed recognition among pupils and students. In his research work – interrupted by his untimely passing – he focused on Roman history, but his studies spanned a broad chronological timeframe and diverse range of topics, namely Roman law (social and constitutional) and military history. He was a man utterly fascinated by his field and working with young people, not to mention his public activism. He was the type of true humanist whose values, formed and embraced during university studies, shaped and permanently influenced his attitude to life. In the final period of his life, with the rise of anti-Semitism and growing threat of war, Zdzisław Zmigryder-Konopka became a member of the National Committee for Aid to Jewish Refugees from Germany. In addition, he became involved with the Social Committee for the Defence of the State as part of the Jewish Community in Warsaw. After the outbreak of the war, he volunteered to fight in the September campaign, and after it ended he arrived in Lwów to become a lecturer at the Jan Kazimierz University. Though affected by poor health and chronic illness, his death on 4 November 1939 still came as a surprise. Discussed more broadly in this paper, Zmigryder-Konopka’s “Battle in the Teutoburg Forest” relied on an analysis of source text to deliver a substantive response to the assertions published in German scholarly literature of the 1930s, which eulogized Germanic past in European history following Germany’s defeat in the Great War of 1914-1918 and Adolf Hitler’s rise to power.